Kunstmuseum Luzern - Jahresbericht der Kunstgesellschaft Luzern 1998. - Bühlmann, Karl; Graf, Walter; Loock, Ulrich; Kunstmuseum Luzern (Luzern : Kunstgesellschaft Luzern, 1999)
Welling, James ; Struth, Thomas ; Bruch, Klaus vom ; Villiger, Hannah ; Havekost, Eberhard ; Döbeli, Markus ; Jobin, Gilles ; Klingler, Monica ; Coste, Annelise ; Leutenegger, Zilla ; Schibli, Daniel ; Vanrunxt, Marc ; De Corte, Marie ; Valle, Truppe Marian del ; Ribot, La ; Ballmer, Karl ; Lichtsteiner, Maria ; Vallotton, Félix
Duits
boek